2010
DOI: 10.1007/978-3-642-17650-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Compromise-Resilient Anti-jamming for Wireless Sensor Networks

Abstract: Abstract. Jamming is a kind of Denial-of-Service (DoS) attack in which an adversary purposefully emits radio frequency signals to corrupt wireless transmissions. Thus, the communications among normal sensor nodes become difficult or even impossible. Although some research has been conducted on countering jamming attacks, few works considered jamming by insiders. Here, an attacker first compromises some legitimate sensor nodes to acquire the common cryptographic information of the sensor network and then jams t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Dong and Liu [9] intro-duced a jamming-resistant broadcast system that organizes receivers into multiple channel-sharing broadcast groups and isolates malicious receivers using adaptive re-grouping. Jiang et al [12] proposed a compromiseresilient anti-jamming scheme called split-pairing to deal with insider jamming in a one-hop network setting. Liu and Ning [17] proposed an encoding method called BitTrickle to defend against broadband and high-power reactive jamming.…”
Section: Countermeasures Against Jammingmentioning
confidence: 99%
“…Dong and Liu [9] intro-duced a jamming-resistant broadcast system that organizes receivers into multiple channel-sharing broadcast groups and isolates malicious receivers using adaptive re-grouping. Jiang et al [12] proposed a compromiseresilient anti-jamming scheme called split-pairing to deal with insider jamming in a one-hop network setting. Liu and Ning [17] proposed an encoding method called BitTrickle to defend against broadband and high-power reactive jamming.…”
Section: Countermeasures Against Jammingmentioning
confidence: 99%
“…Regarding to the scheme in [ 36 ] which studied insider jamming attacks and found that jamming attacks can be carried out by an attacker once a compromised node is exploited to reveal common cryptographic information. To address the insider jamming attacks challenge, a compromise-resilient anti-jamming scheme was proposed.…”
Section: Related Workmentioning
confidence: 99%
“…To clarify, T l is also a channel switch latency for benign nodes. Measurements show that the typical latency is 34ms for Mica2 wireless sensor motes [12] and 7.6ms for Atheros WiFi chipset [13]. For example, for a Mica2 mote with transmission rate of 19.2Kbps, it can transmit 81 bytes during the time when a jammer switches to another channel.…”
Section: B Jamming Modelmentioning
confidence: 99%